MOTIVASI SISWA KELAS VII, VIII, DAN IX DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMPN 5 KEPENUHAN - Yarni, Mukti; Armade, Made; Manurizal, Lolia (Journal Of Sport Education and Training, 2020)
This research aim to know students motivation class VII, VIII and IX at learning Psysical and Healthy study program in SMPN 5 Kepenuhan. This research design is descriptive qualitative. Methode of this research was survey with technique collecting data using quistionare. Subject in this research was students class VII, VIII and IX IN SMPN 1 Kepenuhan with 71 students, from class VII was 30 students, class VIII was 24 students and class IX was 17 Students. Based of result finding can conclude that students motivation class VII,VIII and class IX at learning physical and Healthy study program in SMPN 5 Kepenuhan was middle categories . that categories got from factor intrinsic and exstrinsic . from finding class VII with average from 30 respondent was 92,93 include influenced intrinsic motivation with average score in 30 respondent was 63,20, class VII with average score from 24 respondent was 81,92 include influenced extrinsic motivation with average score from 24 respondent was 58,708, and class IX with average score from 17 respondent was 94,412 include influenced extrinsic motivation with score average from 17 respondent was 62,824. The conclusions from the results of the study show that the motivation of students in grades VII, VIII and IX in learning Physical Education Sports and Health in SMP N 5 Fullness is in the category of "Medium" which is influenced by intrinsic factors and extrinsic factors.